Resilience and digital competences in higher education students - Jaimes Delgado, Pedro Emilio; Pérez Olmos, Liliana Margarita; Celis Salazar, Orlando; Ramírez Pabón, Liliana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Resilience and digital skills could be considered necessary competencies for the individual of the twenty-first century, which the current social reality suggests. For this reason we carried out a research in the institution of higher education -IES- Corporación Escuela Tecnológica del Oriente, of Bucaramanga-Colombia, which had a dual purpose: to describe resilience and digital competence in 356 of its students and establish a comparison between the values of these two aspects and those reported in other HEIs in Mexico, using a quantitative, non-experimental, cross-sectional design and descriptive scope approach, the SV-RES Resilience Scale instrument and a Questionnaire for the study of the Digital Competence of Higher Education Students.